2017
DOI: 10.1038/s41598-017-14119-z
|View full text |Cite
|
Sign up to set email alerts
|

The study on the association between Beijing genotype family and drug susceptibility phenotypes of Mycobacterium tuberculosis in Beijing

Abstract: The predominant prevalent Mycobacterium tuberculosis (M. tb) lineage was the Beijing genotype family in Beijing. There has been no systematic study on the association between drug resistance and Beijing genotype. Here we collected 268 M. tb strains, analyzed the background information and the bacteriological characteristics. The mean age of the cases was 40.12 years; male patients were almost three times than female patients. After genotyping analyzation, 81.7% (219/268) strains were categorized as Beijing gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
4
22
2
Order By: Relevance
“…And they were identified as the causative agents of tuberculosis in the world. For each families of MTB resistance to rifampicin, the prevalence was analyzed for the selected studies as follows: Beijing nineteen studies [14, 15, 16, 17, 18, 19, 20, 21, 22, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31], LAM ten studies [15, 17, 23, 25, 28, 29, 32, 33, 34, 35], T ten studies [3, 15, 16, 17, 23, 27, 28, 32, 34, 35], EAI eight studies [18, 22, 25, 27, 28, 29, 33, 36], Ural four studies [15, 17, 30, 34] Haarlem five studies [15, 23, 25, 28, 34], CAS four studies [15, 29, 30, 35] and MANU two studies [16, 29]. The proportion of rifampicin resistance varies by the type of regions and strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And they were identified as the causative agents of tuberculosis in the world. For each families of MTB resistance to rifampicin, the prevalence was analyzed for the selected studies as follows: Beijing nineteen studies [14, 15, 16, 17, 18, 19, 20, 21, 22, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31], LAM ten studies [15, 17, 23, 25, 28, 29, 32, 33, 34, 35], T ten studies [3, 15, 16, 17, 23, 27, 28, 32, 34, 35], EAI eight studies [18, 22, 25, 27, 28, 29, 33, 36], Ural four studies [15, 17, 30, 34] Haarlem five studies [15, 23, 25, 28, 34], CAS four studies [15, 29, 30, 35] and MANU two studies [16, 29]. The proportion of rifampicin resistance varies by the type of regions and strains.…”
Section: Resultsmentioning
confidence: 99%
“…Eigteen studies reported rifampicin resistance Beijing family. Of these studies, nine were conducted in Western Pacific Region, reported 1309 (97.68%) resistance Beijing family [2, 16, 20, 21, 22, 28, 29, 30, 31], three studies were conducted in South-East Asia Region, reported 15 (1.11%) resistance Beijing family [15, 19, 25], two studies were conducted in European Region and identified 14 (1.04%) resistance Beijing family [17, 24] and two studies were conducted in Region of American but only two resistance Beijing family [18, 23]. One study which was conducted in African Region [29] and one study conducted in Eastern-Mediterranean Region did not report a rifampicin resistance Beijing family [30].…”
Section: Resultsmentioning
confidence: 99%
“…Using spoligotyping the global population of MTB can be classified into four main lineages, lineage 1(Indo-Oceanic lineage), lineage 2 (East-Asian lineages, that includes Beijing family), lineage 3 (East African Indian that includes Central Asian Strain, CAS/Delhi family) and lineage 4 (Euro-American family) 5 . Previous studies have demonstrated a relationship between drug resistance and genotype of MTB 6 8 , while other studies failed to find an association 9 . The Beijing genotype is reported to have unusual characteristics such as hyper-virulence, higher pathogenicity, a greater ability to overcome immunity afforded by BCG vaccination and frequent association with MDR-TB 10 , 11 .…”
Section: Introductionmentioning
confidence: 95%
“…Beijing is confronting public health issues in the prevention and control of TB [4, 27]. The association between the prevalence of Beijing genotype strains and their drug resistance status in Beijing is unclear.…”
Section: Introductionmentioning
confidence: 99%